Evaluation of nutritional knowledge in relation to primary prevention of doctors and nurses in Morocco - Ben Allal, Zohra; Najdi, Adil; El Mlili, Nisrin (Rzeszów University Press, 2025)
Introduction and aim. Currently, Morocco suffers the burden of non-communicable diseases. Healthcare professionals play a crucial role in guiding the population toward healthy dietary choices, which can reduce the risk of these types of diseases. This study aims to assess nutritional knowledge in relation to primary prevention of doctors and nurses working in the hospital network and primary health care facilities in Morocco. Material and methods. The study population consists of 472 nurses and 185 physicians. A self-administered questionnaire composed of four main sections (nutrition by the Mediterranean diet; nutrition for children; nutrition for pregnant and breastfeeding women; and nutrition for the elderly) was used for data collection. Results. The Mediterranean diet obtained the highest score of 0.46 (IQR [0.30, 0.53]) for physicians. But for nurses, the highest score was for child nutrition 0.33 (IQR [0, 0.333]). Our results reveal a statistically significant association of the median total score of answers of health professionals with basic training (p<0.001), receiving information on nutrition (p<0.001), their degree (doctors or nurses) (p<0.001) and the workplace (p<0.001). Conclusion. The training programs of the medical faculties and nursing training institutes in Morocco should be revised in favor of a more in-depth training in nutrition.
Informed consent was obtained from all participants.
Keywords: doctor; health professionals; nurse; nutritional knowledge; primary prevention